2012
DOI: 10.26719/2012.18.11.1091
|View full text |Cite
|
Sign up to set email alerts
|

WHO/INRUD drug prescribing indicators at primary health care centres in Eastern province, Saudi Arabia

Abstract: Appropriate use of drugs is an essential element in achieving quality of health and medical care for patients and the community as a whole. This study aimed to measure the drug prescribing performance of primary health care centres in Eastern province, Saudi Arabia, using the WHO/International Network of Rational Use of Drugs core drug prescribing indicators. In a retrospective cohort study 10 health centres were selected using systematic random sampling. A total of 1000 prescribing encounters were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
12
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(138 citation statements)
references
References 9 publications
12
95
12
5
Order By: Relevance
“…13.4-24.1% [19] and report from south West Ethiopia (11.07%) [21]. However it is lower than study done in Hawasa referral hospital 38.1% [20].…”
Section: Discussionmentioning
confidence: 43%
“…13.4-24.1% [19] and report from south West Ethiopia (11.07%) [21]. However it is lower than study done in Hawasa referral hospital 38.1% [20].…”
Section: Discussionmentioning
confidence: 43%
“…As described in our other paper on the subject [7], indices were calculated for each patient care indicator by dividing the optimal values by the actual values obtained. All the indicators had the same optimal index of 1: the closer to 1, the more rational a drug use indicator.…”
Section: Discussionmentioning
confidence: 99%
“…In Yemen, the rate of prescribing drugs by generic name was low (39.2%), the proportion of prescriptions for antibiotics was high (66.2%) and availability of an essential drugs list (EDL) was only 78.9% [6]. In a previous paper we reported a survey of rational drug prescribing in 10 primary health care centres (PHCCs) in Eastern province of Saudi Arabia [7]. The study reported here also used the WHO/ International Network of Rational Use of Drugs (INRUD) criteria to assess the performance of the same PHCCs in terms of patient care and facility-specific drug use indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to gauge the drug utilization performance of this hospital, indices for rational prescribing and rational patient care indicators were calculated accordingly. The optimal values of all indicator studies were standardized to 1 [12][13][14]. Among the prescribing indicators, indices for non-polypharmacy, rational antibiotic utilization and injection safety were calculated by formula (1) Index = optimal value (standard) Observed value (actual setting) (…”
Section: Data Processing and Analysismentioning
confidence: 99%